(untitled) - Rimando, Tito J. (Laguna, Philippines, 2001)
This book is intended for agricultural students who have taken some basic courses in botany, chemistry, crop protection, and soil science, hence, some topics were dealt with more as a review. Emphasis was made on aspects relevant to the production and utilization of ornamental plants
Keywords: Ornamental horticulture; Vocational guidance